PROFESSIONALLY IMPORTANT QUALITIES OF PERSONALITY: SOCIAL AND PEDAGOGICAL DISCOURSE (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
Based on theoretical and methodological background and contemporary research, the essence and content of the concept of 'professionally significant personal qualities' are essential for the acquisition of special knowledge, skills and abilities, in order to achieve efficiency in professional activity, because preparation of a modern successful specialist is impossible without proper training and mastering knowledge and skills of both fundamental and applied nature; the assimilation of universal moral principles and norms; proper level of moral culture and professionally significant qualities; independent orientation in non-standard situations; the ability to solve effectively certain issues in the professional field and modern society.It is substantiated that professionally significant qualities characterize abilities, belong organically to their structure, develop in the process of learning, professional activity, socialization. Summing up the various views of scientists, the notion of 'professionally meaningful personality qualities' and their role in self-realization of the personality in the socio-cultural space are defined. The list of necessary professionally relevant qualities is proposed to be developed taking into account the specifics of each individual organization and each individual position, in accordance with the specifics of the company's activities and corporate culture (organizations, institutions, enterprises, etc.).
Keywords: professionally significant personal qualities, professional qualities, personal qualities, abilities, socio-cultural space, social- pedagogical discourse.